Constitutional Principles of Judiciary and Justice in the Russian Federation: Current Regulation and Status - Kremyanskaya, Elena Alexandrovna; Kuznetsova, Tamara Olegovna; Rakitskaya, Inna Alexandrovna (International Journal of Psychosocial Rehabilitation, 2020)
The present article is devoted to the analysis of regulation and content of the principles of judiciary and justice in the Russian Federation which are declared in the Constitution and federal laws of. These principles stipulate basic procedural rights belonging to anyone facing an adjudicative process or procedure that affects fundamental rights and freedoms, and certain substantive standards related to the rule of law that regulate the actions of the state. The authors analyze the interrelation between the concepts of “principles of justice” and “principles of judicial power”, describe the institutionalization of the judiciary in Russia taking into account constitutional reforms latest held in 2014. The article is based on the current legislation, as well as Russian doctrinal sources.